2016
DOI: 10.1088/0741-3335/58/11/114005
|View full text |Cite
|
Sign up to set email alerts
|

ELM control with RMP: plasma response models and the role of edge peeling response

Abstract: Resonant magnetic perturbations (RMP) have extensively been demonstrated as a plausible technique for mitigating or suppressing large edge localized modes (ELMs). Associated with this is a substantial amount of theory and modelling efforts during recent years. Various models describing the plasma response to the RMP fields have been proposed in the literature, and are briefly reviewed in this work. Despite their simplicity, linear response models can provide alternative criteria, than the vacuum field based cr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
122
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(131 citation statements)
references
References 88 publications
7
122
0
2
Order By: Relevance
“…A closer analysis reveals that the large X-point displacement is a sufficient but not a necessary condition when the edgepeeling response is dominant-a more general condition is the weak equilibrium poloidal field along the certain poloidal angle of the plasma surface. 19 The edge-peeling response criterion is particularly useful in providing guidance for optimization of the RMP coil phasing, as has been demonstrated in MAST, ASDEX Upgrade, and EAST in the previous work, and in the detailed modelling for HL-2A in this study. Extensive modeling has also shown that the optimal coil phasing depends on the plasma conditions, in particular, on the edge-q value (q 95 ) as well as on the plasma pressure.…”
Section: Conclusion and Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…A closer analysis reveals that the large X-point displacement is a sufficient but not a necessary condition when the edgepeeling response is dominant-a more general condition is the weak equilibrium poloidal field along the certain poloidal angle of the plasma surface. 19 The edge-peeling response criterion is particularly useful in providing guidance for optimization of the RMP coil phasing, as has been demonstrated in MAST, ASDEX Upgrade, and EAST in the previous work, and in the detailed modelling for HL-2A in this study. Extensive modeling has also shown that the optimal coil phasing depends on the plasma conditions, in particular, on the edge-q value (q 95 ) as well as on the plasma pressure.…”
Section: Conclusion and Discussionmentioning
confidence: 70%
“…14 All the modelling results, in comparison with the corresponding experimental observations, so far point to the important role played by the edge-peeling response for achieving the best ELM mitigation. 19 The edge-peeling response, which was first identified in modelling of the JET experiments, 34 is found to be closely correlated to the pronounced plasma surface displacement near the X-point. On the contrary, the other type of the plasma response-the core-kink response-often causes large plasma displacement near the outboard mid-plane, due to the ballooning effect.…”
Section: Modelling Elm Mitigation Experimentsmentioning
confidence: 85%
See 3 more Smart Citations